Curative remnant total pancreatectomy for recurrent pancreatic acinar cell carcinoma: A case report. (May 2022) - Hiyoshi, Masahide; Kai, Kengo; Hamada, Takeomi; Yano, Koichi; Imamura, Naoya; Nanashima, Atsushi
Abstract: Introduction and importance: Acinar cell carcinoma (ACC) of the pancreas is a rare pancreatic cancer subtype (incidence, 0.5–2%) with unclear epidemiology and prognosis. Sometimes, repeat resection including total pancreatectomy is required for recurrence. We report a case of ACC recurring in the remnant pancreatic head after distal pancreatectomy that was successfully cured by remnant pancreatic resection following combination therapy with nab-paclitaxel (nab-PTX) and gemcitabine (GEM). Case presentation: A 64-year-old woman was referred for pancreatic tumour treatment. CT revealed a 46-mm tumour in the pancreatic body, and endoscopic ultrasonography-guided fine needle aspiration (EUS-FNA) indicated ACC. Distal pancreatectomy was performed, and the final diagnosis was ACC. CT 18 months later showed a 34-mm tumour in the remnant pancreatic head revealed as ACC by EUS-FNA. Portal vein invasion was apparent, so neoadjuvant chemotherapy with nab-PTX and GEM was administered, and remnant pancreatic resection (total pancreatectomy) was performed. No recurrence or distant metastasis was present more than 6 months later. Clinical discussion: Mean survival time for ACC is 18–47 months, and prognosis is good compared with pancreatic ductal adenocarcinoma (PDAC). ACC tends to extend and grow along the main pancreatic duct, which increases the recurrence rate to 50–60%. EUS and EUS-FNA were useful for evaluating tumour extension and diagnosis. Repeat pancreatic resection that included total pancreatectomy was feasible and could be performed safely. Conclusion: ACC has a better prognosis than PDAC but with a higher recurrence rate. Aggressive surgical resection that included remnant total pancreatotomy with chemotherapy was useful in treating ACC. Highlights: Acinar cell carcinoma (ACC) of the pancreas is a rare type of pancreatic tumour. ACC has good prognosis compared with pancreatic ductal adenocarcinoma, but the recurrence rate is high. Surgical resection that includes remnant pancreatic resection is useful for pancreatic tumours. Neoadjuvant and adjuvant chemotherapy are useful in treating ACC.